2019
DOI: 10.1136/bjophthalmol-2019-314706
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a commercial spectral-domain OCT and swept-source OCT based on an angiography scan for measuring circumpapillary retinal nerve fibre layer thickness

Abstract: Background/aimsTo assess the agreement in measuring retinal nerve fibre layer (RNFL) thickness between spectral-domain (SD; Cirrus HD, Carl Zeiss Meditec, USA) optical coherence tomography (OCT) and swept-source (SS; Plex Elite 9000, Carl Zeiss Meditec) OCT using an OCT angiography (OCTA) scanning protocol.Methods57 participants (12 glaucomatous, 8 ocular hypertensive and 74 normal eyes) were scanned with two OCT instruments by a single experienced operator on the same day. Circumpapillary RNFL thicknesses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
14
1
Order By: Relevance
“…Incorporating both components of the retinal microvasculature and retinal ganglion cell axons [ 9 ] may further improve the screening performance of OCTA for cognitive impairment. We had previously shown that the structural component of the retina can be extracted from OCTA system with good reliability [ 61 ]. Nevertheless, there are many important considerations when determining whether some form of screening for cognitive impairment in older adults is worthwhile [ 62 ]; these include the technical challenge of motion artifacts in OCTA scans.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating both components of the retinal microvasculature and retinal ganglion cell axons [ 9 ] may further improve the screening performance of OCTA for cognitive impairment. We had previously shown that the structural component of the retina can be extracted from OCTA system with good reliability [ 61 ]. Nevertheless, there are many important considerations when determining whether some form of screening for cognitive impairment in older adults is worthwhile [ 62 ]; these include the technical challenge of motion artifacts in OCTA scans.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons were made using only circumpapillary parameters, and the use of retinal capillary density and macular ganglion cell thickness could provide more insight into the structure–function relationship, 8 , 24 , 54 particularly with recent widefield retinal imaging protocols. Different machines were used to generate measurements of the RNFL thickness and the OCT-A perfusion parameters, although Tan et al 55 recently showed that there was excellent agreement between the two machines for RNFL measurement. Most of the subjects in our study had VF MD of better than –6 dB, and evaluation of the structure–function model in subjects with more severe glaucoma was limited.…”
Section: Discussionmentioning
confidence: 99%
“…In this study also found eccentricity and keratometry, along with several other corneal parameters, that can detect glaucomatous visual field damage. While the association between myopia and glaucoma is well studied 53 , 54 , follow-up studies may be merited to further examine the association between keratoconus and glaucoma, as our studies suggest that several corneal parameters such as spherical aberration coefficients exist that can predict both conditions.…”
Section: Discussionmentioning
confidence: 85%